Assessing the effectiveness of UMP STEM cube as a tool for developing digital making skill sets - Nurul Hazlina, Noordin; Kamil Khalili, Abdullah; Eu, Phuah Soon (Institute of Electrical and Electronics Engineers Inc., 2024)
This study presents an innovative experiential learning model utilizing an educational pico satellite kit as a tool for cultivating digital making skills. The distinct approach showcases a positive impact on students’ learning experiences and serves as a motivating force, offering valuable implications for engineering and technical education. In response to the dynamic technological landscape and escalating demand for digital making skills, this research addresses the need for cutting-edge educational tools. The UMP STEM Cube, strategically designed to elevate hands-on learning in digital making, emerges as a promising applicable solution across diverse educational programs. An experiential learning module that elevates digital making skills in engineering education, specifically focusing on programming competencies and proficiency in physical computing. This study conducts an evaluation of the UMP STEM Cube’s influence on experiential learning and skill development. The instructional approach of employing the UMP STEM Cube aligns with Kolb’s Experiential Learning Theory. The modular design of the UMP STEM Cube bridges the theoretical–practical gap in digital making education, fostering a holistic and impactful learning experience. This study establishes a correlation between hands-on engagement with the UMP STEM Cube and a significant learning gain in programming competencies and physical computing skills among students. Participants’ positive perceptions, better competency in programming, and increased interest in digital making activities further emphasizes the efficacy of the UMP STEM Cube in fostering digital making skill sets.